Could plant extracts have enabled hominins to acquire honey before the control of fire?. Issue 85 (August 2015) - Kraft, Thomas S.; Venkataraman, Vivek V.
Abstract: Honey is increasingly recognized as an important food item in human evolution, but it remains unclear whether extinct hominins could have overcome the formidable collective stinging defenses of honey bees during honey acquisition. The utility of smoke for this purpose is widely recognized, but little research has explored alternative methods of sting deterrence such as the use of plant secondary compounds. To consider whether hominins could have used plant extracts as a precursor or alternative to smoke, we review the ethnographic, ethnobotanical, and plant chemical ecology literature to examine how humans use plants in combination with, and independently of, smoke during honey collection. Plant secondary compounds are diverse in their physiological and behavioral effects on bees and differ fundamentally from those of smoke. Plants containing these chemicals are widespread and prove to be remarkably effective in facilitating honey collection by honey hunters and beekeepers worldwide. While smoke may be superior as a deterrent to bees, plant extracts represent a plausible precursor or alternative to the use of smoke during honey collection by hominins. Smoke is a sufficient but not necessary condition for acquiring honey in amounts exceeding those typically obtained by chimpanzees, suggesting that significant honey consumption could have predated the control of fire.